Persian Girls - Nahid Rachlin (American Studies Journal, 2011)
Nahid Rachlin spent her childhood in Iran under the Shah regime. In the following paragraphs that are drawn from her memoir Persian Girls, she introduces the reader to a hidden and risky world of bookstores in Tehran during that very period. Hence, she openly describes how she was “drawn to books, hoping to find answers to what I could not make sense of.” Ultimately, the desire to read leads to a desire to learn and to write. Managing to attend college in the US, Nahid Rachlin, however, has to experience that in a society were books are freely available and writers are free to exercise their profession, people can yet be bigots, too.